Chief Justice W.R. Jackett : by the law of the land - Pound, Richard W. (McGill-Queen's University Press, 1999)
After graduating from the University of Saskatchewan's College of Law, Jackett was chosen as a Rhodes Scholar. He returned to Canada from Oxford not long before the outbreak of World War II and joined the ten-man Department of Justice as a junior lawyer. Through extraordinary hard work, rigorous legal analysis, and a bent for organization, he eventually became Canada's eighth deputy minister of Justice. He left this position after three years to become general counsel for the Canadian Pacific Railway and was later appointed president of the Exchequer Court of Canada. He quickly revamped the level of service provided by the court to the legal profession and the public and was instrumental in both the creation of the Canadian Judicial Council and the design and creation of the new Federal Court of Canada. As the first chief justice of the Federal Court, he led the new court by example, moulding it into the most efficient and effective court in the country, despite opposition from provincial superior courts and the Supreme Court of Canada. After fifteen years on the Bench he retired in 1979 at the height of his judicial career, believing that this would help the Court develop. He continued to work in relative obscurity at what he loved best - solving legal problems - but never again appeared before the courts.